Juridical Analysis of Data Sovereignty in the Era of Digital Economy in Indonesia - Judijanto, Loso; Suwarna, A. Idun; Putra, Irman (The Easta Journal Law and Human Rights, 2025)
The rapid growth of digital platforms has given rise to new challenges in the protection of privacy rights, particularly in cases of digital slander. This study explores the intersection of privacy protection and digital slander dissemination in Indonesia, focusing on the impact of post-truth dynamics. Using a normative juridical approach, the research examines Indonesia’s legal framework, including the 1945 Constitution, the Electronic Information and Transactions Law (ITE Law), and the Personal Data Protection Law (PDPL), to evaluate the effectiveness of legal mechanisms in safeguarding individuals' privacy in the digital space. The study identifies key gaps in privacy protection, particularly in the context of the post-truth environment, where misinformation and emotional manipulation often overshadow factual accuracy. Comparative analysis with international legal frameworks highlights best practices that could inform reforms in Indonesia. The study concludes with recommendations for legal reforms aimed at enhancing privacy protection and addressing the complexities of digital slander in the era of post-truth.